2017
DOI: 10.1016/j.trgeo.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of subballast reinforced with used tyre and potential application in rail tracks

Abstract: Rubber tyres have a three dimensional cylindrical structure, and as such could be used to stabilise foundations by increasing the bearing capacity and reducing settlement for transport infrastructure. It is therefore expected that in railroad engineering, a capping layer reinforced with rubber tyres could help to reduce the thickness of the granular layer (i.e. ballast), improve the track bearing capacity, and reduce the frequency of maintenance. However, there is a notable gap between the conceptual theories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…The FEM results of the load-deformation relationships for tyre confined and unconfined plate load tests agreed reasonably well with the experimental results as shown in Figure 12 (Indraratna, Sun and Grant 2017). Having calibrated the FEM model with a single tyre unit, a plane strain section of half a ballasted substructure was simulated to examine how the foundation would react under load, with or without being confined by tyres.…”
Section: Finite Element Analysis Of Railway Track With Rubber Tyre-resupporting
confidence: 67%
“…The FEM results of the load-deformation relationships for tyre confined and unconfined plate load tests agreed reasonably well with the experimental results as shown in Figure 12 (Indraratna, Sun and Grant 2017). Having calibrated the FEM model with a single tyre unit, a plane strain section of half a ballasted substructure was simulated to examine how the foundation would react under load, with or without being confined by tyres.…”
Section: Finite Element Analysis Of Railway Track With Rubber Tyre-resupporting
confidence: 67%
“…Fig. 4a shows the load vs. strain curves of the 231 five materials obtained from tension tests (Henkel and Gilbert 1952;Koerner 2012;Biabani 232 2015; Indraratna et al 2017;Lal et al 2017 Similar behavior is observed in the direction of σ'2. The magnitude of kσ,2 is the highest 252 for rubber tire followed by HDPE, coir geotextile, polypropylene geotextile and rubber 253 membranes.…”
mentioning
confidence: 59%
“…The investigations in the past have demonstrated the beneficial 52 role of geocells (e.g., Raymond 2001;Satyal et al 2018) and scrap tires (e.g. Forsyth and Egan 53 1976; Garga and O'shaughnessy 2000;Indraratna et al 2017) in improving the stability of 54 railway tracks and embankments. However, the lack of a well-established method to evaluate 55 the magnitude of additional confinement provided by these geoinclusions has limited their 56 application in the railway tracks.…”
Section: Introductionmentioning
confidence: 99%
“…Indraratna et al (2017) proposed a rubber tire based capping layer for railway track where one sidewall is removed and the tire is then filled with gravel; a geotextile can be placed between the rubber tire and the ground as a separator. Plate load tests (Indraratna et al, 2017) and prototype process simulation carried out by Indraratna et al (2018) revealed that a tire cell has three primary engineering benefits: (i) the confinement provided by the cellular assembly can increase the stiffness of the contained aggregate, which then reduces lateral spreading and vertical deformation within the capping and ballast layers; (ii) the tires and gravel composites allow a reduced and more uniform stress distribution to the subgrade; and (iii) tire cells can enhance the damping properties of the system, and thus its ability to attenuate dynamic forces imposed by rail traffic. However, since the dimensions are limited by the size of the experimental facility (i.e., 800 × 600 × 600 mm), a light vehicle tire having a diameter of 560 mm was tested.…”
Section: Introductionmentioning
confidence: 99%
“…These models were based on the assumption that substructure materials are purely elastic and this will lead to inaccurate prediction. Recently, a finite element 3D model has been developed to investigate the load transfer mechanism between tires and infill gravels under static loading (Indraratna et al, 2017). It was reported that the confining effect causes the tire and gravel infill composite to act as a stiff but flexible "mattress" that can effectively reduce the amplitude of stresses transmitted to the subgrade.…”
Section: Introductionmentioning
confidence: 99%